CO2 capture from air and its conversion to CH4 using dual functional materials supported on high surface area graphite - Jorge Moral-Pombo; Enrique García-Bordejé; Yuefeng Liu; Antonio Guerrero-Ruiz; Inmaculada Rodríguez-Ramos (Journal of CO2 Utilization)
Several cycles of CO2 capture from synthetic air containing 400 ppm of CO2 and subsequent conversion to CH4 have been performed using dual functional materials consisting of 4 wt% Ru and 10 wt% Ba or Cs supported on a high surface area graphite. The effect of the presence of humidity and the regeneration conditions have been assessed. The presence of moisture in the air enhances CO2 capture. The capture material is not properly regenerated in the absence of H2-containing atmosphere or at temperatures below 300 ºC. The exhaustive characterization by XRD, XPS, TEM and temperature programmed reduction and reaction allowed to shed some light about the reasons of the different behavior of Ba and Cs based dual functional materials. Cs is more efficiently utilized than Ba, providing higher CO2 capture capacities (0.44 mmol g−1) and CH4 productivity (0.41 mmol g−1). The outperformance of Cs is attributed to the more homogeneous and better dispersed species which are regenerated at lower temperatures.